Associations between cognition and serotonin receptor 1B binding in patients with major depressive disorder – A pilot study. (30th September 2017) - Tangen, Ämma; Borg, Jacqueline; Tiger, Mikael; Varnäs, Katarina; Sorjonen, Kimmo; Lindefors, Nils; Halldin, Christer; Lundberg, Johan
Abstract: The neurotransmitter serotonin has been widely implicated in the pathophysiology of major depressive disorder (MDD). In animal studies and human neuroimaging studies, involvement of the serotonin receptor 1B (5-HT1BR) in MDD and memory performance has been reported. However, the role of the 5-HT1BR in cognitive functions affected in MDD remains to be clarified. Ten patients with MDD diagnosis were examined with positron emission tomography (PET) and a battery of cognitive tests before and after Internet-based Cognitive Behavioral Therapy (ICBT). The results were compared to ten matched control subjects in order to investigate putative changes in 5-HT1BR availability and cognitive performance. Patients treated with ICBT showed statistically significant improvement relative to baseline in Verbal fluency, both letter and category production. Significant correlations were found between improvement in letter production and changes in 5-HT1BR availability in ventral striatum, between category production and amygdala, as well as between the improvement in Trailmaking test B and change in 5-HT1BR binding in dorsal brainstem, in amygdala and in hippocampus. The results suggest an association between 5-HT1BR binding and improvement in cognitive functioning. Replications in larger-scale studies are required to confirm these findings. Highlights: Verbal fluency improved after Internet-based CBT in patients with MDD. Significant correlations were found between cognitive ability and 5-HT1BR binding. Changes in cognitive performance were correlated with changes in 5-HT1BR binding after ICBT treatment.